2005
DOI: 10.1097/01.mlg.0000163101.12933.74
|View full text |Cite
|
Sign up to set email alerts
|

Program Directors??? Opinions about Surgical Competency in Otolaryngology Residents

Abstract: Surgical skill is one aspect of clinical competency, and this indicates agreement among program directors with regard to a set of benchmark skills we can use for concentrated evaluation efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…It is acknowledged that competency may be achieved at different rates by different individuals [24]. In addition, competency does not equal expertise.…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that competency may be achieved at different rates by different individuals [24]. In addition, competency does not equal expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [1,2,3 , [4][5][6][7][8]9 ] have examined the role of training programs in teaching stapes surgery. Yung et al…”
Section: Trainingmentioning
confidence: 99%
“…In a survey among 73 US otolaryngology program directors, Carr [9 ] found 60% of program directors agree that PGY-5 residents are competent as primary surgeons when performing stapedectomy. Though respondents felt that residents should perform an average of 10.5 stapedectomies to establish competence, graduate case-logs from 2002, as reported to the American Board of Otolaryngology, revealed the average graduate performed 6.8 stapedectomies.…”
Section: Trainingmentioning
confidence: 99%
“…Studies have shown that 10–15 operative procedures are needed for technical and basic competency in mastoidectomy 48,49 . However, proficiency in surgical procedures requires substantially more practice—up to 100 procedures—but often at the cost of patient discomfort, longer procedural times and increased risk of complications 50 .…”
Section: Introductionmentioning
confidence: 99%